Pharmacokinetics and Tolerability of Etamicastat Following Single and Repeated Administration in Elderly Versus Young Healthy Male Subjects: An Open-Label, Single-Center, Parallel-Group Study - Nunes, Teresa; Rocha, José Francisco; Vaz-da-Silva, Manuel; Falcão, Amilcar; Almeida, Luis; Soares-da-Silva, Patricio (Clinical therapeutics, 2011)
Etamicastat is a new dopamine-β-hydroxylase (DβH) inhibitor currently in clinical development for the treatment of hypertension and heart failure. To evaluate the pharmacokinetics and tolerability of etamicastat after single and repeated administration in elderly subjects (aged ≥65 years) relative to young adult healthy controls (aged 18–45 years). This was a single-center, open-label, parallel-group study in young male adults (n = 13; mean [SD] age 32.6 [16.4] years; range, 18–44 years; weight 79.0 [16.4] kg; systolic blood pressure 117 [12] mm Hg and diastolic blood pressure 61 [7] mm Hg) and 12 elderly male volunteers (n = 12; age 69.3 [3.3] years; weight 69.2 [9.5] kg; systolic blood pressure 115 [13] mm Hg and diastolic blood pressure 64 [4] mm Hg), conducted in 2 consecutive periods. All subjects were white, except for 1 black elderly subject. In Phase A, subjects received a single dose of 100 mg etamicastat. In Phase B, subjects received 100 mg/d etamicastat for 7 days. The pharmacokinetic parameters of etamicastat and its acetylated metabolite BIA 5-961 were calculated after the single dose of Phase A and the last dose of Phase B. Subjects' N-acetyltransferase type 1 (NAT1) and type 2 (NAT2) genotyping was performed and acetylator status inferred. After a single dose of etamicastat 100 mg, mean (SD) plasma C max and plasma AUC 0–∞ were, respectively, 1.3 (0.5) ng/mL/kg and 12.4 (7.8) ng × h/mL/kg in elderly subjects, and 1.3 (0.4) ng/mL/kg and 10.0 (6.6) ng × h/mL/kg in young subjects. At steady-state, C max and AUC 0–24 were 1.8 (0.5) ng/mL/kg and 15.0 (6.4) ng × h/mL/kg in elderly subjects, and 1.5 (0.7) ng/mL/kg and 12.5 (6.5) ng × h/mL/kg in young subjects. Elderly/young geometric mean ratios and 90% CIs were, respectively, 0.944 (0.788–1.131) and 1.164 (0.730–1.855) for etamicastat C max and AUC 0–∞ after a single dose, and 1.225 (0.960–1.563) and 1.171 (0.850–1.612) for etamicastat C max and AUC 0–24 at steady state. Etamicastat steady-state plasma concentrations were reached after 3 to 4 days of dosing. The mean etamicastat accumulation ratio was 1.7 in both age groups. Following etamicastat single dose, mean (SD) BIA 5-961 C max and AUC 0–∞ were, respectively, 3.5 (2.1) ng/mL/kg and 28.4 (14.7) ng × h/mL/kg in elderly subjects, and 2.5 (1.5) ng/mL/kg and 16.5 (9.7) in young subjects. At steady state, BIA 5-961, C max, and AUC 0–24 were 4.3 (2.6) ng/mL/kg and 34.6 (17.6) ng × h/mL/kg in elderly subjects, and 3.1 (2.0) ng/mL/kg and 22.2 (11.8) ng × h/mL/kg in young subjects. Large interindividual variability dependent on the NAT2 acetylator status was found in the pharmacokinetic parameters of etamicastat and BIA 5-961. Systemic exposure to etamicastat was higher and systemic exposure to BIA 5-961 was lower in NAT2 poor metabolizers compared with rapid metabolizers. No effect on heart rate and blood pressure was found in the young group. In the elderly, a decrease of supine blood pressure was observed. Postural changes in blood pressure were unaffected. Four adverse events (AEs) were reported by each group: nasopharyngeal pain, sciatica, asthenia, and back pain the elderly group, and headache (2 cases), insomnia, and myopericarditis by the young group. Myopericarditis led to study discontinuation for this subject and was considered to be of probable viral etiology. All other AEs were mild to moderate in intensity. The pharmacokinetic profile of etamicastat was not significantly different in these small groups of healthy young versus elderly adult male volunteers.